International students' alienation in a US higher education institution. Issue 2 (10th June 2019) - Pepanyan, Marine; Meacham, Sohyun; Logan, Stephanie
Abstract : Purpose: The purpose of this study is to focus on the difference between perceptions of single and married international students. Four aspects are discussed to explain this issue: comfort level of international students in a host environment, their cultural representation, language competence/barrier and major challenges related to the host community. Then their attachment process was discussed. Design/methodology/approach: The study deployed a qualitative research methodology with purposeful sampling to gain a closer insight into the trails, experiences, feelings and perceptions of international students. Findings: The findings in this qualitative research underscore the importance of the individual's will to adjust to the host society, at the same time to preserve the valuable sense of ethnic and personal identity for each foreign student. The focus group interviews reveal that domestic students, are not necessarily hostile towards international students, but simply do not know how to approach them without intruding in and violating the privacy and cultural norms of international students. Research limitations/implications: This qualitative study had only eight participants, which may hinder generalizability of findings. Future studies with survey methods to look into international students' perceptions can be supplementary to the authors' study. Practical implications: Quantitative studies with a significant number of international students' perceptions rather than standardized scores or administrative records can provide an important layer in the literature body. This way, future research can unpack individual differences regarding social alienation with more nuances. Social implications: The research does not generalize the students' experiences by classifying them into ethnic groups or representatives. However, it could be informative to look into same country population reflections, too. Originality/value: This study is focused on the students' marital status seeking to understand a pattern that may differentiate the sociocultural acclamation or alienation processes, exploring their socializations within academic (e.g. classmates and professors) or nonacademic contexts (e.g. on or off-campus social/affinity groups), racial–ethnic sensitivity and perceived pressure and stereotypes among foreign students.